Hydropower Generation in Malaysia: A review and some notes - Chee, Wah Yap; Chee, Kong Yap (Universal Wiser Publisher, 2023)
The objective of this paper was to discuss the future potential of Hydropower Generation (HG) in Malaysia based on available publications published between 1970 and 2021 in the Scopus database (12 papers) and non-Scopus (3 papers). Out of the 15 papers reviewed, it was found that 73% of papers studied and discussed the economic aspect of the HG in Malaysia, while 27-47% studied and discussed the social and environmental aspects although some could merge with the economic factor. This paper indicated the economic aspect as primary importance in the hydropower studies and construction in their planning processes until full implementation of this Renewable Energy (RE) in Malaysia. This analysis shows that Large (> 10 MW) Hydropower System (HPS) papers only covered 31% of the 12 papers (discarding the 2 unspecified papers) reviewed in this study, while the rest (69%) covered mostly Micro (< 100 kW) HPS (46%), followed by Mini (< 1 MW), Small (< 10 MW), and Pico (< 5 kW) HPSs. It is almost certain, the Micro HPS or lower capacities of HPS hold the bright future in the reduced costs of energy consumption in Malaysia with special reference to economic factors that would boost the social development the betterment of well-being of the nation.